The Use of Project-Based Science Learning Model to Improve Critical Thinking Skills of Elementary School Students - Melani, Echa Rizki; Triwoelandari, Retno; Imamah, Ade Irma (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2025)
In elementary science education, approaches that actively engage students in thinking and problem-solving processes are highly needed. One learning model considered effective for this purpose is project-based learning. This study aims to examine the effectiveness of this model in enhancing students' critical thinking skills. The research employed a mixed-methods experimental design with a pretest-posttest control group. The subjects were fifth-grade students at an Islamic elementary school (SDIT) in Bogor Regency. The instruments included descriptive questions to measure critical thinking abilities and interview and observation guides to explore student and teacher responses. Quantitative analysis revealed a significant difference between the experimental and control groups, with average posttest scores of 82.5 and 74.3, respectively (p < 0.05). Qualitative data showed increased student enthusiasm, active discussions, and a more enjoyable learning process. This study contributes to the development of more meaningful and contextual science teaching strategies, highlighting significant differences compared to previous studies that have not deeply emphasized critical thinking skill development.